SAÚDE MENTAL E BUCAL: conexões invisíveis entre esquizofrenia, medicamentos e a perda dentária - Maia Koch Torres, Samantha; Afonso Miranda, Valtair; Maia Koch Torres de Andrade, Gabriela; Vieira Fonseca de Almeida, Charlles (LINKSCIENCEPLACE, 2026)
This study addresses the relationship between mental health and oral health, which has been attracting increasing interest in the scientific community, especially with regard to severe disorders such as schizophrenia. The aim of this study is to understand the impact of schizophrenia on oral health and to investigate the effects of psychiatric medications on dentition. It seeks to promote a more comprehensive understanding of mental and oral health, in addition to contributing to the development of preventive and therapeutic strategies. Research indicates that people with schizophrenia face substantial challenges in maintaining oral health, with high incidences of cavities, periodontitis, and tooth loss. These problems are often aggravated by side effects of antipsychotic medications, which can cause xerostomia (dry mouth) and metabolic changes. In addition, inadequate oral hygiene practices, limited access to health services, and social stigma also intensify these vulnerabilities. The research was conducted using a qualitative approach, aiming at an in-depth analysis of the topic. This study is classified as exploratory and descriptive, with the objective of identifying and describing the main factors associated with the relationship between schizophrenia and oral health. The data collected were evaluated through a narrative synthesis, identifying patterns, gaps in the literature and the consequences of the interactions between mental and oral health. This study aimed to enrich the academic field by exploring the intersection between mental health and dentistry, providing support for integrated clinical practices and public policies that consider the specificities of this relationship. Through this study, it was found that it is necessary to promote strategies that promote a more comprehensive and humanized approach in the health care of individuals with schizophrenia.